2017
DOI: 10.1016/j.dyepig.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable prodrugs of butyric acid based on new coumarin fused oxazole heterocycles

Abstract: New coumarin fused oxazoles were investigated as photosensitive units for carboxylic acid groups using butyric acid as a model compound. 6-Oxo-6H-benzopyrano[6,7-d]oxazol-8yl)methyl derivatives possessing various (hetero)aromatic substituents at position 2 of the heterocyclic system were used in the synthesis of ester conjugates of butyric acid. Photolysis at selected wavelengths in methanol/HEPES buffer (80:20) solutions, monitored by HPLC/UV and 1 H NMR, produced the complete release of butyric acid. The sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Benzocoumarin derivatives typically have similar or slightly hypsochromically shifted absorption maxima relative to 4-methyl­coumarin ,, (λ max abs = 274–321 nm vs 310 nm), but their spectroscopic properties can be modified by introducing EDGs or EWGs to modulate their ICT states . Gonçalves, Costa, and co-workers reported on several benzocoumarin PPGs ( 63 – 68 ); their structures and photophysical and photochemical properties relating to the photorelease of various carboxylic acids are shown in Table . , …”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 96%
See 1 more Smart Citation
“…Benzocoumarin derivatives typically have similar or slightly hypsochromically shifted absorption maxima relative to 4-methyl­coumarin ,, (λ max abs = 274–321 nm vs 310 nm), but their spectroscopic properties can be modified by introducing EDGs or EWGs to modulate their ICT states . Gonçalves, Costa, and co-workers reported on several benzocoumarin PPGs ( 63 – 68 ); their structures and photophysical and photochemical properties relating to the photorelease of various carboxylic acids are shown in Table . , …”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 96%
“… 490 Gonçalves, Costa, and co-workers reported on several benzocoumarin PPGs ( 63 – 68 ); their structures and photophysical and photochemical properties relating to the photorelease of various carboxylic acids are shown in Table 11 . 320 , 491 500 …”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“…Chung et al ( 2013 ) also analyzed the effect of coumarin on polymer model stating that the increase in coumarin functionality resulted in decreasing nanoparticle size and polydispersity and increased the stability of the polymer in water. Hence, Soares et al ( 2017 ) examined light-sensitive moieties for releasing bioactive molecules by combining coumarin with oxazoles using butyric acid resulting in a shorter irradiation time at a longer wavelength (11 min, at 350 nm), thus demonstrating coumarin can enhance the photo-cleavage of the prodrug. A combination of coumarin with (6-bromo-7-methoxycoumarin)-nicotinamide reported by Bourbon et al ( 2013 ) also showed photo-cleavage upon irradiation.…”
Section: Mechanisms Of Uva-induced Drug Releasementioning
confidence: 99%
“…Among the polyheterocycles, poly oxygenated heterocycles have gained considerable attention because of their presence in many marketed drugs [4] . In particular, complex motifs of tetracyclic oxazoles found in natural products, synthetic bioactive molecules, and exhibit diverse therapeutic profiles and have valuable applications in materials science [3a,5] . Although few synthetic methods towards tricyclic oxazoles have been reported in the literature, [6,7] but synthetic methods for the synthesis of complex tetracyclic oxazoles are scarcely reported [8] .…”
Section: Introductionmentioning
confidence: 99%